2015
DOI: 10.1123/japa.2014-0081
|View full text |Cite
|
Sign up to set email alerts
|

Strength, Static Balance, Physical Activity, and Age Predict Maximal Gait Speed in Healthy Older Adults From a Rural Community: A Cross-Sectional Study

Abstract: Regardless of the model, KStrength60° was the best predictor of MGS in rural female older adults. Future research should examine the generalization of these findings to rural male older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Age‐related changes in gait patterns include slower gait speed, shorter stride length, wider step width, lower step rate and longer double support time . These changes are affected by physical functional factors, such as decreased muscle strength and poor balance, but also by psychological factors . One of the psychological factors related to decreasing gait performance is fear of falling (FOF).…”
Section: Introductionmentioning
confidence: 99%
“…Age‐related changes in gait patterns include slower gait speed, shorter stride length, wider step width, lower step rate and longer double support time . These changes are affected by physical functional factors, such as decreased muscle strength and poor balance, but also by psychological factors . One of the psychological factors related to decreasing gait performance is fear of falling (FOF).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another study reported that isometric knee extensor strength explained 36% of the variance of comfortable gait speed among a sample of 839 older adults [18]. Balance has also been shown to influence gait speed through assessment of various components of standing balance [14][15][16][17].…”
Section: Introductionmentioning
confidence: 93%
“…Current literature recognizes a number of influencing variables on gait speed including balance [14][15][16][17], lower extremity muscle strength [14,15,18,19], cognition [20][21][22], and demographic characteristics (e.g. age) [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging causes a decline in the level of physical function 1) . This decline often leads to difficulties in locomotion, e.g walking, getting out of a chair, and stair climbing [2][3][4] . It may originate from disease, life style, psychosocial and socio-demographic factors, genetic predisposition or a combination of the above 5) .…”
Section: Introductionmentioning
confidence: 99%